Effect of quantitative assessment‐based nursing intervention on the bowel function and life quality of patients with neurogenic bowel dysfunction after spinal cord injury. Issue 5 (25th March 2018) - Zhang, Yanyan; Xia, Xiyan; Zhuang, Xuewei
Abstract : Aims and objectives: To study the effect of quantitative assessment‐based nursing intervention on the bowel function and life quality of patients with neurogenic bowel dysfunction after spinal cord injury. Background: Neurogenic bowel dysfunction after spinal cord injury was clinically manifested by abdominal distension, intractable constipation, prolonged defecation and faecal incontinence, which seriously affected the normal life of patients. Traditional ways of nursing for these patients focused on basic care, but lacked sufficient recognition of disease severity and individual needs. Design: One hundred and eighty‐four patients with neurogenic bowel dysfunction after spinal cord injury were randomly allocated into observation group ( n  = 92) and control group ( n  = 92). Methods: The patients in the control group were given regular nursing, and the patients in the observation group were given quantitative assessment‐based nursing intervention. Recovery of bowel function, quality of life and satisfaction were compared between the two groups. Results: Scores for bowel function including bloating, constipation, prolonged defecation, defecation drug dependence and faecal incontinence in the observation group were significantly lower than those in the control group ( p  <   .05). The scores for the quality of life including physical function, general health, social functioning, role‐motional, mental health in the observation group were significantly higher than those in the control group ( p  <   .001). Finally, the satisfaction rate in the observation group was 95.56%, which was significantly higher than that in the control group (83.7%) ( p  <   .01). Conclusion: We concluded that quantitative assessment‐based nursing intervention contributed to recovery of bowel function and improvement of life quality and satisfaction. Relevance to clinical practice: Our finding can increase the rational allocation of nurse–patient ratio and provide personalised nursing for severe patients to reduce complications and promote the rehabilitation of the disease. Our findings can also serve as a reference for other countries to develop the nurse practitioner role.